Synthesis of ZnO Nanoparticles by Bacillus subtilis for Efficient Photocatalytic Degradation of Cyanide - Alberto Bacilio Quispe Cohaila; Gabriela de Lourdes Fora Quispe; Wilson Orlando Lanchipa Ramos; César Julio Cáceda Quiroz; Rocío María Tamayo Calderón; Jesús Plácido Medina Salas; Saravanan Rajendran; Elisban Juani Sacari Sacari (Nanomaterials)
This study presents a sustainable and scalable biosynthesis method for zinc oxide (ZnO) nanoparticles using Bacillus subtilis, focusing on their application in photocatalytic cyanide degradation in aqueous solutions. The bacterial strain was molecularly identified through 16S rRNA gene sequencing and phylogenetic analysis. The optimized biosynthesis process yielded crystalline ZnO nanoparticles in the zincite phase with an average size of 21.87 ± 5.84 nm and a specific surface area of 27.02 ± 0.13 m2/g. Comprehensive characterization confirmed the formation of high-purity hexagonal ZnO (space group P63mc) with a bandgap of 3.20 eV. Photocatalytic tests under UV irradiation demonstrated efficient concentration-dependent cyanide degradation, achieving 75.5% removal at 100 ppm and 65.8% at 500 ppm within 180 min using 1.0 g/L ZnO loading. The degradation kinetics followed a pseudo-first-order model with rate constants ranging from 6.64 × 10−3 to 3.98 × 10−3 min−1. The enhanced photocatalytic performance is attributed to the optimal crystallite size, high surface area, and surface defects identified through a microscopic analysis. These results establish biosynthesized ZnO nanoparticles as promising eco-friendly photocatalysts for industrial wastewater treatment.